Perlindungan Hukum Terhadap Data Privasi Konsumen E-Commerce Yang Menjadi Korban Kejahatan Siber - Pontorondo, Immanuel; Walangitan, Misael Aldo; Rondonuwu, Bervie Fransel (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Technology has become a vital part of Indonesian business activities. Currently in Indonesia, regulations regarding e-commerce are regulated in Law Number 11 of 2008 which has been amended to Law Number 19 of 2016 concerning Electronic Information and Transactions, Law Number 7 of 2014 concerning Trade and Government Regulation Number 80 of 2019 concerning Trade through Electronic Systems. In this research, the method used is normative research method, which in its construction includes analyzing problems by managing data obtained from laws and regulations (statue approach) as the basis of research. Seeing the rapid progressiveness of technology, e-commerce transactions have become an integral part of people's lives. This progress can be seen in transaction tools that only use electronic goods through financial applications which have now become a platform for conducting trading activities. In conclusion, consumers as data subjects are also given significant legal rights. In Articles 7-13 of the Personal Data Protection Law, various data subject rights are mentioned, including the right to obtain information regarding the clarity of the identity of the party requesting the data, the right to access and correct the data, the right to erasure, and the right to withdraw consent. The exercise of these rights becomes a juridical instrument to control the use of the data.